2018
DOI: 10.1002/ente.201800300
|View full text |Cite
|
Sign up to set email alerts
|

A facile Solvent/Nonsolvent Preparation of Sintering‐Resistant MgO/CaO Composites for High‐Temperature CO2 Capture

Abstract: For CaO‐based high‐temperature CO2 sorbents, excellent cyclic stability is highly desired for its practical applications. Among all techniques, preparation of CaO‐based composites is one of the most widely accepted strategies, and the mixing status between CaO and the inert supporting material is crucial for its anti‐sintering property. This work provides a new strategy for preparing nanometrically dispersed MgO/CaO composites with significantly improved cyclic stability. The so called solvent/nonsolvent synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Huang et al developed a new and facile solvent-nonsolvent method for the preparation of MgO/CaO composites, which retain 95.3% of its initial capacity aer seven cycles. 21 Ping et al prepared MgO-coated CaO-based adsorbent. They found that the thickness of the coating layer could be modied by varying MgO content, and the optimum amount of CO 2 adsorption was 36.1 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al developed a new and facile solvent-nonsolvent method for the preparation of MgO/CaO composites, which retain 95.3% of its initial capacity aer seven cycles. 21 Ping et al prepared MgO-coated CaO-based adsorbent. They found that the thickness of the coating layer could be modied by varying MgO content, and the optimum amount of CO 2 adsorption was 36.1 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonation cycles were carried out under 20% CO 2 at 650 °C, and decarbonation cycles under 100% N 2 at 700 °C. The initial assessment of the first 10 CO 2 capture cycles (Figure b and Table ) points to the fact that porous CaO and stabilized CaO–MgO of all compositions display relatively high capture capacities and cycling stabilities in comparison to literature reports. ,,,,,, Among the porous structures, pristine CaO exhibits a near theoretical capacity of 0.768 g CO 2 / g sorbent . In the case of CaO–MgO sorbents, as the percentage of the stabilizer MgO increases, the capture capacity decreases linearly as expected due to a decrease in the CaO content, but the increase in the cycling stability (Table ) reiterates the role of the stabilizer to resist sintering due to volume changes …”
Section: Resultsmentioning
confidence: 78%
“…The initial assessment of the first 10 CO 2 capture cycles (Figure 4b and Table 2) points to the fact that porous CaO and stabilized CaO−MgO of all compositions display relatively high capture capacities and cycling stabilities in comparison to literature reports. 5,12,30,33,40,41,52 Among the porous structures, pristine CaO exhibits a near theoretical high capture capacity and almost no loss in efficiency after 10 cycles, appears to be promising. Due to its initial high capture capacity and cycling stability, CaO 80 −MgO 20 was subjected to 100 carbonation−decarbonation cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Conceptually, a stabilization of the cyclic performance of a CaO-based sorbent can be achieved with every type of metal oxide, provided its melting point is higher than that of CaCO3, its solubility in CaO is low and (ideally) it does not interact chemically with CaO. Accordingly, oxides of the elements Mg, Y, La, Ce, Pr, Yb and Nd have previously been investigated as potential stabilizers for CaO with varying success [163], [286], [291], [350], [361]- [365].…”
Section: Inert Stabilizersmentioning
confidence: 99%